The Effect of Intranasal Splint on Prevention of Adhesion After Septoplasty - Khayat , Farhad Jalil; Yaseen , Abdulmajeed (Diyala Journal of Medicine, 2019)
Background: Intranasal adhesion is one of the common complications following nasal surgeries. Using nasal splint during the surgery is one of the methods for prevention of this complication. Objectives: To determine the value of intranasal splints in preventing adhesion formation after septoplasty. Patients and methods: This is a prospective study done in Rizgary Teaching Hospital - Erbil city from 1st August 2010 to 31st January 2011. Sixty patients included in this study. Their age range were18-38 years old. Intranasal splint used during septoplasty in half of them. Follow up done for all patients at same interval. Results: Intra nasal adhesion developed in one patient (3.5%) of splinted group, while adhesions occurred in three patients (10.0%) of non splinted group. One patient (3.5%) among male while three patients (10.0%) among females developed intranasal adhesion. One patient (3.0%) among those with right septal deviation while three patients (10.5%) among those with left septal deviation had adhesion. There was no difference in Adhesions development in both sides of the septum. Conclusion: There is no statistically significant difference in intranasal adhesion development between splinted and non splinted group and no statistically significant influence of the gender and side of septal deviation on the adhesion formation.